ANALISIS KURIKULUM 2013 DENGAN KURIKULUM MERDEKA DI MADRASAH IBTIDAIYAH - Hodijah, Eneng; Budi, Asep; M. Sudi, Didih; Hasan Ansori, Ari; Inayatulloh, Siti (Staisman Press, 2024)
This study discusses the differences between the 2013 curriculum and the independent curriculum in Madrasah Ibtidaiyah. The research aims to describe the changes that occur in the curriculum, so that the differences between the 2013 curriculum and the independent curriculum will be seen. The method used in this research is descriptive qualitative method with data collection such as interviews, observations and analysing documents to get in-depth information. In addition, researchers also used literature studies from several books. Curriculum and learning are two things that cannot be separated. Curriculum will not be meaningful if it is not implemented in the form of teaching. The curriculum is a plan and arrangement of learning programmes that include material, teaching methods, and evaluation of learning outcomes to achieve educational goals. The curriculum used today is the independent curriculum. However, this independent curriculum has not been fully used in madrasah institutions because it is still in the transition stage from the previous curriculum, namely the 2013 curriculum or what is often called K-13. The results of this analysis reveal significant differences between the 2013 curriculum and the independent curriculum. Both in terms of making teaching tools, teaching methods, and evaluation. It is hoped that this difference in curriculum can have a positive impact that will break the world of education in Indonesia. The impact on learners from the implementation of the 2013 curriculum may have more of an impact on learner involvement and motivating learners. Whereas the independent curriculum has an impact on the level of engagement of participants through different learning approaches. This is reinforced by the findings in the field, namely at Madrasah Ibtidaiyah Darul Huda Leuwipapan, that students are more active and creative with the implementation of the independent curriculum. Although this curriculum is still not evenly distributed in units of educational institutions and is not one hundred per cent optimal.